Disruption of glucocorticoid signalling in osteoblasts attenuates age-related surgically induced osteoarthritis. Issue 10 (October 2019) - Tu, J.; Zhang, P.; Ji, Z.; Henneicke, H.; Li, J.; Kim, S.; Swarbrick, M.M.; Wu, Y.; Little, C.B.; Seibel, M.J.; Zhou, H.
Summary: Objective: Aging is a major risk factor for osteoarthritis (OA). Skeletal expression and activity of the glucocorticoid-activating enzyme 11β-hydroxysteroid-dehydrogenase type 1 increases progressively with age in humans and rodents. Here we investigated the role of endogenous osteocytic and osteoblastic glucocorticoid (GC) signalling in the development of osteoarthritic bone and cartilage damage in mice. Methods: We utilized transgenic (tg) mice in which glucocorticoid signalling is disrupted in osteoblasts and osteocytes via overexpression of the glucocorticoid-inactivating enzyme, 11β-hydroxysteroid-dehydrogenase type 2. Osteoarthritis was induced in 10- and 22-week-old male transgenic mice (tg-OA, n = 6/group) and their wildtype littermates (WT-OA, n = 7–8/group) by surgical destabilization of the medial meniscus (DMM). Sham-operated mice served as controls (WT- & tg-Sham, n = 3–5 and 6–8/group at 10- and 22-weeks of age, respectively). Results: Sixteen weeks after DMM surgery, mice developed features of cartilage degradation, subchondral bone sclerosis and osteophyte formation. These changes did not differ between WT and tg mice when OA was induced at 10-weeks of age. However, when OA was induced at 22-weeks of age, cartilage erosion was significantly attenuated in tg-OA mice compared to WT-OA littermates. Similarly, subchondral bone volume (−5.2%, 95% confidence intervals (CI) -9.1 to −1.2%, P = 0.014) and osteophyte size (−4.0 mm 2, 95% CI -7.5 to −0.5 mm 2, P = 0.029) were significantly reduced in tg-OA compared to WT-OA mice. Conclusion: Glucocorticoid signalling in cells of the osteoblast lineage promotes the development of surgically-induced osteoarthritis in older, but not younger, male mice. These data implicate osteoblasts and osteocytes in the progression of DMM-OA, via a glucocorticoid-dependent and age-related pathway.